2022
DOI: 10.1088/1742-6596/2265/2/022061
|View full text |Cite
|
Sign up to set email alerts
|

Do ambient shear and thermal stratification impact wind turbine tip-vortex breakdown?

Abstract: Modern wind turbines experience uneven inflow conditions across the rotor, due to the ambient flow’s shear and thermal stratification. Such conditions alter the shape and length of turbine wakes and thus impact the loads and power generation of downstream turbines. To this end, understanding the spatial evolution of the individual wakes under different atmospheric conditions is key to controlling and optimising turbine arrays. With this numerical study we aim to obtain a better understanding of the fundamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…As can be expected, higher shear causes the helical tip vortices to convect more quickly at the top than at the bottom resulting in a tilting of this flow structure. A proper orthogonal decomposition (POD) analysis, as performed by Hodgkin et al [10] for a wind turbine in shear and explained in [22], would show that the tip vortices can be identified as the dominant helical mode with an associated frequency and wavelength. In Fig.…”
Section: Turbine Performancementioning
confidence: 99%
See 3 more Smart Citations
“…As can be expected, higher shear causes the helical tip vortices to convect more quickly at the top than at the bottom resulting in a tilting of this flow structure. A proper orthogonal decomposition (POD) analysis, as performed by Hodgkin et al [10] for a wind turbine in shear and explained in [22], would show that the tip vortices can be identified as the dominant helical mode with an associated frequency and wavelength. In Fig.…”
Section: Turbine Performancementioning
confidence: 99%
“…The near-wake structure can be classified in three regions: linear, transition and turbulent based on the tip vortex behavior described above and as proposed in [10]. Note that, in our work, the classification is based only on visual inspection over a range of iso-surfaces.…”
Section: Turbine Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The presence of high wind shear has a twofold impact on wake evolution and turbine performance, affecting wake size, shape, and recovery, and impacting loads and power output [8]. Hodgkin et al [9] demonstrated that shear significantly impacts the evolution of tip vortices and, consequently, the shape of the wake. Furthermore, wind shear and turbulence can lead to the formation of highly complex wake structures downstream of the turbine rotor, characterized by significant asymmetries, streamwise vorticity generation, nonperiodicity, and non-uniformity [10].…”
Section: Introductionmentioning
confidence: 99%